The Entrepreneurial Readiness Mindset of Generation Z at SMK Negeri 1 Tambusai: What Is The Relationship? - Belyarosa Dwi Putri; Putu Sudira (International Forum of Researchers and Lecturers, 2025)
The unemployment rate in Indonesia, especially among Generation Z, is still very high, especially among Vocational High School (SMK) graduates. The purpose of this study is to explore the entrepreneurial mindset and entrepreneurial readiness of Generation Z at SMK Negeri 1 Tambusai. The research was conducted using survey method through questionnaires involving 78 students of grade X and XI of Fashion Design and Production Department. The results showed that the majority of students have a high entrepreneurial mindset with 30% of students showing a very high mindset and 26% with a high mindset. In addition, entrepreneurial readiness is also at a high level with 18% of students showing very high readiness and 51% with high readiness. These results are in line with previous research which shows that growth mindset and entrepreneurship education play an important role in improving entrepreneurial readiness.